THE SECRETARIAT/MINISTRY OF JEWISH AFFAIRS AND THE JEWISH NATIONAL COUNCIL IN THE CONTEXT OF THE CONSTRUCTION OF NATIONAL AND PERSONAL AUTONOMY (July 1917 – April 1918) - Лазарович, М.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
Analyzed the basic principles of activities and the structure of the Secretariat/Ministry of Jewish Affairs and the Jewish national council. Then traced especially their functioning and cooperation. Defined by achievement of both institutions, primarily in the legislative, institutional and cultural spheres, gaining experience of state-building.